2004
DOI: 10.5367/0000000042664774
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Saharan African Agricultural Research

Abstract: Following two decades of increasing investments, growth in public agricultural research spending in Sub-Saharan Africa stagnated during the 1980s and 1990s at an average rate of about 1% per year. Nonetheless, this continent-wide trend masks significant variation among countries. During 1991-2000, about half the countries in the authors' 27-country sample experienced negative annual growth in total agricultural research and development (R&D) spending. Declines often resulted from political unrest or the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Kenya spent about 1.43 percent of agricultural GDP on research and development, which is almost twice Sub-Saharan Africa's level of 0.7 percent (Beintema and Stads 2004;Flaherty et al 2008). Crop breeding and research in other management practices contributed to the increased crop yield (Smale and Jayne 2008).…”
Section: Success Stories Of Kenyamentioning
confidence: 99%
“…Kenya spent about 1.43 percent of agricultural GDP on research and development, which is almost twice Sub-Saharan Africa's level of 0.7 percent (Beintema and Stads 2004;Flaherty et al 2008). Crop breeding and research in other management practices contributed to the increased crop yield (Smale and Jayne 2008).…”
Section: Success Stories Of Kenyamentioning
confidence: 99%
“…It cut agricultural investments in SSA during that period by 57%, to about $US 80 million. By 2000, African agriculture received less US development assistance than any other sector 18 . This has led to a continuing decline in agricultural productivity.…”
Section: Globalisation Agriculture and Foodmentioning
confidence: 99%
“…Agricultural productivity per worker for the region as a whole has fallen by about 12% since 1980. Growth in agricultural output has arisen mostly from expansion in the area under cultivation, encroaching onto fallow lands and leading to significant reductions in soil fertility 18 . Significantly, the yields of most important food grains, tubers and legumes in most African countries are no higher today than in 1980.…”
Section: Globalisation Agriculture and Foodmentioning
confidence: 99%
“…Moreover, the underdeveloped transport systems and infrastructure have significantly limited the capacity of developing national and regional markets for agricultural products, thereby allowing greater competitiveness for foreign products (Hazell and Diao, 2005). More recently, it has been observed that African agricultural policies have tended to enhance comparative advantages for specific cash crops, at the expense of subsistence agriculture on which most of the smallholders depend (Beintema and Stads, 2004).…”
Section: Agriculturementioning
confidence: 99%
“…First, we note that most of the institutions lack the financial, technical and human resources to enable the management of their territory. Second, agricultural R&D is declining in half of the SSA countries (Beintema and Stads, 2004), putting at risk their ability to produce the necessary information for the implementation of sustainable land management policies. In the following section we seek to analyze the state of knowledge, the quantification of C stocks, C flows and the contribution from deforestation and forest degradation.…”
Section: Underlying Factors Of Forest Degradation and Deforestationmentioning
confidence: 99%